The Pittsburgh Study: Learning with Communities About Child Health and Thriving (Mary Ann Liebert, 2022)
The COVID-19 pandemic has highlighted structural inequities that are barriers to thriving for children in neighborhoods with concentrated disadvantage. Health systems are increasingly addressing health-related social needs. The ?Pittsburgh Study? is a longitudinal, community-partnered study focused on child and adolescent thriving and racial equity. This initiative will elucidate critical influences on childhood health and thriving, evaluate developmentally appropriate interventions to improve outcomes from birth to high school, and establish a child health data hub. Integration of community members into scientific inquiry, rapid data-to-action cycles, and workforce development are strategies health systems may consider to enhance child health equity.